Impacts of nickel mining activities on coastal ecosystems: An analysis of interactions between human activities and geological systems - Yazeed Titan Yudhaprawira (Journal of Earth Kingdom, 2026)
Background: Rising nickel demand has accelerated nickel mining expansion in Indonesia, a major lateritic nickel supplier. Upland disturbance can intensify erosion and sediment delivery, stressing coastal ecosystems and communities dependent on coastal resources. Existing assessments commonly treat erosion–sedimentation processes and downstream socio-ecological impacts separately, leaving the mechanism linking upland disturbance to coastal consequences insufficiently integrated. Methods: This study developed a mechanistic conceptual model within a Social–Ecological Systems (SES) framework using a conceptual–analytical, literature-based design. A PRISMA-informed workflow selected 30 documents, which were analysed through thematic coding, causal mapping, and SES mapping. Findings: Six recurring process themes emerged: land disturbance; geomorphic mediation (runoff → erosion → sediment transport); sediment connectivity; changes in resource units (turbidity, total suspended solids [TSS], and water quality); decline in coastal resource-system functions; and social consequences moderated by governance. In tropical archipelagic settings, short upstream–downstream distances and high rainfall can shorten ecosystem response times. Where mining mobilises fine lateritic sediment fractions, the reviewed literature suggests that they may contribute to prolonged turbidity and stored sediment that can later be resuspended, potentially delaying ecological recovery. Conclusion: These mechanisms are indicative patterns requiring site-specific field validation. The model supports integrated watershed–coastal management, using turbidity/TSS as an analytical-threshold early-warning indicator supported by monitoring, enforcement, rehabilitation, and governance response capacity. Novelty/Originality of this article: This study explicitly embeds erosion, sediment transport, and sediment connectivity as the mechanistic bridge linking nickel-mining disturbance to coastal ecological and livelihood risks within a single SES-based pathway.